THE ROLE OF MATRIX METALLOPROTEINASES IN PROCESSES OF HEART RE-MODELING IN CHILDREN WITH RESTRICTIVE CARDIOMYOPATHY - T.V. Bershova; A.G. Gasanov; A.P. Ivanov; E.V. Basargina; M.I. Bakanov; R.B. Zurabova (Вопросы современной педиатрии, 2009)
Restrictive cardiomyopathy (RCMP) is heart disorder with unclear etiology; it can be characterized as disease with disorder of diastolic myocardium function of left ventricle, conditioned by restriction. The chronic heart failure as a syndrome of RCMP can develop as a result of disbalance in system of complex biochemical, structural, and geometrical mechanisms of myocardium re-modeling. Extra cellular matrix play significant role in heart structure and geometry breaking. The destruction of heart is realized by matrix metalloproteinases (MMP). The activity of MMP, in its turn, is controlled by its tissue inhibitors. The present study analyzed the role of MMP in process of collagen’s synthesis and catabolism deregulation, myocardium fibrosis, change of heart chambers, and development of diastolic dysfunction in children with RCMP.Key words: children, chronic heart failure, restrictive cardiomyopathy, matrix metalloproteinases.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(5):36-39)